A study on the macroeconomic factors affecting demand for life insurance industry in Malaysia / Siti Rosmaslina Ajan - Ajan, Siti Rosmaslina (Faculty of Business and Management, 2007)
This study investigates the macroeconomic factors affecting demand for life insurance industry in Malaysia. Because the macroeconomic factors have an imponanl influence on life business and this area has not been grmtly researched in Malaysia, this study is undertaken to examine the demand for life insurance industry in Malaysia. This study further examines the significant relationship between income, inflation rate and price of insurance as the independent variables with the demand for life insurance industry in Malaysia as the dependent variable. All the data used are in annual basis range from the year 1972 until year 2005‘ In analyzing the data, Multiple Linear Regression Model is used, The major findings of this study indicate that income, inflation rate and price of insurance show positive insignificant relationship with the demand for life insurance industry in Malaysia. Further research is needed in this respect in order to confirm the relationship between of these three variables.